Gambaran Self Care Management pada Pasien yang Menjalani Kemoterapi - An Nud Khayun; Indah Sri Wahyuningsih; Mohammad Arifin Noor (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Chemotherapy is an effective treatment for the destruction of cancer cells, but often causes side effects that affect the quality of life of patients, such as nausea, vomiting, hair loss, and fatigue. Chemotherapy patients need physical and psychological motivation to overcome these side effects. In these side effects, self-equipment is the key to treating and improving symptoms properly. The purpose of this study aims to determine how to manage self-care in patients undergoing chemotherapy. Quantitative research with a descriptive design Data were collected through purposive sampling techniques on 230 respondents. And statistical tests were used to process the data. Of the 230 respondents, most were women (53 percent), with an average age of 56-63 years (54.8%), the most recent education was PT/Academic (46.5%), most of the jobs were civil servants (32.2%), had undergone chemotherapy for <1 year (56.1%), the most cancer stage was stage IV (30%) and for the most side effects experienced hair loss/weight loss (42.2%). In this study, self-care management in the adaptive category was (66.5%) and in the maladaptive category (33.5%). It can be concluded that self-care management is very effective in reducing the side effects of chemotherapy.